2002
DOI: 10.1007/s00248-002-2002-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Prochlorococcus and Synechococcus Consumption by Bacterivorous Nanoflagellates

Abstract: We compared the characteristics of ingestion of Prochlorococcus and Synechococcus by the marine heterotrophic nanoflagellate Pseudobodo sp. and by a mixed nanoflagellate culture (around 3 microm in size) obtained from an open sea oligotrophic area. Maximum ingestion rate on Synechococcus (2.7 Syn flagellate(-1) h(-1)) was reached at concentrations of 5 x 10(5) Syn mL(-1) and decreased between 6 x 10(5) and 1.5 x 10(6) Syn mL(-1). In order to validate laboratory data, one set of data on Synechococcus grazing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 51 publications
8
73
1
Order By: Relevance
“…This may indicate a grazer saturation concentration for which grazers (if only ingesting Synechococcus) are no longer food-limited and can achieve their maximum division rates. For nanoflagellates observed in other studies, these end-bloom concentrations appear to be just slightly below ingestion saturation concentrations [20,109].…”
Section: Spring Bloommentioning
confidence: 50%
See 2 more Smart Citations
“…This may indicate a grazer saturation concentration for which grazers (if only ingesting Synechococcus) are no longer food-limited and can achieve their maximum division rates. For nanoflagellates observed in other studies, these end-bloom concentrations appear to be just slightly below ingestion saturation concentrations [20,109].…”
Section: Spring Bloommentioning
confidence: 50%
“…This broad term encompasses the heterotrophic nanoflagellates, ciliates, and dinoflagellates, all which have been reported to feed on Synechococcus [21,15,85,20,44] and may be important classes of grazers at MVCO. These organisms can quickly react to and take advantage of an increase in prey cells as their own cell division rates can match or exceed those of Synechococcus [52].…”
Section: Relationships Between Division Rate and Loss Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, during warm seasons, Synechococcus spp. shows distinct diel changes in abundance, with higher division rates at dusk (Dolan and Šimek 1999;Christaki et al 2002;Tsai et al 2009) and maximum abundances at night (Christaki et al 2002;Tsai et al 2008Tsai et al , 2009). Therefore, Synechococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…abundance is less than 1 × 10 4 cells mL -1 during low temperatures when there are no clear diel variations in abundance (Tsai et al 2008). Christaki et al (2002) reported that heterotrophic nanoflagellate (HNF) grazing on Synechococcus spp. is the highest at night and declines during the daytime in oligotrophic open-sea areas.…”
Section: Introductionmentioning
confidence: 99%